Design of the neutron slit package for Femi chopper prototype of CSNS - GUO Juan; CAI Weiliang; GENG Yansheng; WANG Ping; ZHANG Hong (He jishu, 2021)
BackgroundFermi chopper is the key equipment for monochromating the neutron beam in an inelastic neutron scattering spectrometer, and its performance will affect the resolution and counting rate of the spectrometer. The core component of Fermi chopper is neutron slit package, which is composed of neutron absorbing material and transparent material, and selects multiple single wavelength pulsed neutrons by high-speed rotation.PurposeThe study aims to design suitable slit packages for Fermi chopper prototype of China spallation neutron source (CSNS).MethodsAccording to the common experimental conditions of inelastic scattering, the development target of the Fermi chopper prototype was determined, then three typical slit packages were designed, and the feasibility of the design was verified by MCStas software simulation.ResultsThe simulation results show that: (1) the three kinds of slits can achieve a resolution of 2%~10% in the wavelength range of 0.02~0.50 nm, and the neutron decay rate and the slit packet transmittance meets the requirements; (2) the optimal incident wavelengths of the three kinds of slit packets at 600 Hz operating frequency are 0.165 nm, 0.040 nm and 0.023 nm respectively, which can be used in different wavelength ranges; (3) in the long wavelength band with better resolution, the slit packet can be used to reduce the velocity and improve the neutron pass rate.ConclusionsThe physical parameters for the prototype development of CSNS Fermi chopper are given by this study, it provides a reference for the slit package performance test of the future prototype, as well as the design of the neutron slit package of the Fermi chopper of the inelastic scattering spectrometer.